Meta-analysis about gamified learning experience in Physical Education - Prieto Andreu, Joel Manuel (Revista Complutense de Educación, 2023)
The meta-analysis allows us to know how gamification has been approached through different physical education didactic proposals from 2015 to 2021. For the writing of the meta-analysis, the protocols of the PRISMA 2020 declaration were followed. Following the results, 47 significant studies were identified a through a systematic search in wos, scopus and scholar google. The relevance of the scientific production is analyzed according to six evaluation criteria: number of times cited, application of gamification, methodological coherence, contribution to the area of knowledge, argumentative clarity and methodological rigor. The initial evidence indicates that gamification has been explored in physical education under didactic experiences that in their construction can be differentiated in terms of several aspects: the methodology used is gamification to a greater extent, followed by game-based learning, serious games and exergames, and video games; Regarding support, the most used in the studies analyzed in the review were, in descending order: non-digital, blended learning, digital-pc and digital mobile/tablet; Regarding character, the most used were: cooperative-competitive, collaborative, cooperative and competitive; Finally, the most used types of games were: active learning games, games with mechanics based on points, badges and leaderboards, awareness games, virtual teaching platforms, role-playing games, puzzle games, strategy games and board games. The characteristics of the gamified proposals included in the meta-analysis are discussed.